Communication Strategies in Change Management and Their Influence on Employee Engagement - Wahyudi (Jurnal Ragam Pengabdian, 2026)
Changes in work systems and organizational policies demand the implementation of effective change management, where communication strategies are a key factor in building employee engagement. However, in practice, change communication is often not optimally managed, hindering the creation of sustainable employee engagement, especially in private companies operating in dynamic business environments. This study aims to analyze the influence of communication strategies in change management on employee engagement by emphasizing the relative role of each dimension of change communication. The study uses a quantitative approach with an explanatory survey design. Data was collected through a structured questionnaire on the Likert scale of 120 employees of medium- and large private companies in Semarang City who experienced changes in work systems and organizational policies. Data analysis was carried out using multiple linear regression to test the influence of information clarity, communication openness, message consistency, two-way communication, and communication media on employee engagement. The results show that communication strategies in change management have a positive and significant effect on employee engagement, with clarity of information and two-way communication emerging as the most decisive dimensions. These findings indicate that the effectiveness of change communication does not only depend on the intensity of information delivery, but on the quality of message clarity and dialogue space provided to employees. This research provides an empirical contribution by emphasizing the importance of configuring a change communication strategy oriented to transparency and participation in strengthening employee engagement in private companies in the local context of Indonesia.